2020
DOI: 10.1155/2020/8812470
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Deformation Mechanism of Soft Rock Roadway considering the Mine Water

Abstract: The existence of coal mine water has an important influence on the instability of soft rock roadway in mining engineering. Considering the effect of mine water, a case study on the fracture mechanism and control technology of soft rock roadway was performed in this paper. The results showed that with the increase of moisture content, the uniaxial compressive strength of mudstone nonlinearly decreased, while the tensile strength, Young’s modulus, cohesion, and friction angle tended to a linear decrease approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moisture content can also be an additional complicating factor. Mentioned before and scholars [20,21] studied the influence of water content on floor heave. However, in this paper this factor is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture content can also be an additional complicating factor. Mentioned before and scholars [20,21] studied the influence of water content on floor heave. However, in this paper this factor is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Wen (Wen et al, 2021) investigated the support method for large section soft rock roadway and obtained the displacement, plastic zone, and stress field distribution law of the surrounding rock by numerical simulation. By using the numerical simulation inversion, Chen (Chen et al, 2020) reported that as the moisture content increases, the failure zone further extends to the deep surrounding rock, leading to increased stress relaxation around the roadway, especially in the roof. Wei (Zhu et al, 2022b) proposed a new concept of internal and external self-bearing structures for the surrounding rock and determined the shape of the internal and external bearing structures based on the results of field monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Mining disturbance also contributes to a dramatic deformation of the roadway [21,22]. Water-based erosion in a water-rich roadway reduces its strength and serviceability [23,24]. Bottom dilation is a common feature for the deformation of soft rock roadways [25][26][27].…”
Section: Introductionmentioning
confidence: 99%